Preservice Primary Teachers' Depth and Accuracy of Knowledge of Tropical Cyclones. Issue 5 (2nd September 2016) - Lane, Rod; Catling, Simon
Abstract: Climatic hazards are a key feature of life. It is vital that teachers are knowledgeable about these phenomena in order to develop their students' understanding of them. This study used a mixed methods approach to examine the accuracy and depth of preservice primary teachers' (n = 430) knowledge of tropical cyclones. The findings suggest that prospective primary teachers hold alternative conceptions about the causes, spatial distribution, and impacts of these phenomena and that their explanations of processes lack structural complexity and integration. Issues raised by these findings and implications for teachers' geographical knowledge and their professional standards and preservice teacher education are discussed.